Redescription of the adult stages of Ixodes (Afrixodes) rasus Neumann 1899, with notes on its phylogenetic position within the genus Ixodes - D'Amico, G; Estrada-Peña, A; Kalmár, Z; Fuh, T; Petrželková, K; Mihalca, A D (Ticks and tick-borne diseases, 2018)
The tick subgenus Afrixodes Morel 1966 (Ixodidae) is distributed in sub-Saharan Africa. It consists of about 60 species which are described based on a few specimens and/or only some developmental stages, mostly adults. Because of this, the diagnosis of the African species of Ixodes is in many aspects complicated. Ixodes rasus Neumann 1899 is a common species, widely distributed in tropical and subtropical moist broadleaved forests in central Africa, whose morphology remains poorly described. We redescribe the adults of the species and provide molecular data for 16S rDNA based on three questing females and one male collected in the Central African Republic. Both sexes have an anal groove rounded and closed. The female has syncoxae on coxae I to III, a dental formula of 2/2, and long, curved auriculae. The male has moderate syncoxae on coxae I-III, coxae I-II carry one single internal spur each: coxae III and IV unarmed. The cornua are absent in the male, and the auriculae are small lobes. The male pregenital plate is longer than broad, with an anterior margin widely rounded; the median plate is large and clearly divergent posteriorly, with adanal plates fused posteriorly to the anus, and a dental formula of 4/4 (one row of 5/5). The molecular features of 16S rDNA place I. rasus near I. aulacodi (the only other Afrixodes species for which 16S rDNA is available) and near I. turdus and I. frontalis; two species of ticks of the Palearctic region, which commonly infest birds. The paucity of data regarding the subgenus Afrixodes makes it necessary to provide reliable and comparable re-descriptions of several species, as well as description of the immature stages for many of the currently known taxa.
Keywords: RNA, Ribosomal, 16S; nymfa; 16S rDNA; Ixodes; Central African Republic; mužské pohlaví; ženské pohlaví; RNA ribozomální 16S; zvířata; Nymph; Ixodidae; fylogeneze; Středoafrická republika; Redescription; larva; Larva; klíště; Female; Phylogeny; Ixodes rasus; Male; Animals